Appraising the Ecotourism Potentials of the Knuckles forest Reserve to Preserve its Sustainability - Ruzaik, Fareena (University of Ruhuna, Sri Lanka, 2023)
Ecotourism is nature-based visits with the anticipation of enjoying natural attractions, learning, education, environmental protection and maintaining sustainability. The Knuckles Mountain Range was acknowledged as a ‘world’s heritage’, considering its historical value, geological and geomorphological features, ecological diversity and richness of biodiversity within the area of 160-170 km2. This study was carried out with the objective of assessing its existing potentials to promote ecotourism, while preserving its sustainability. Both primary and secondary data sources have been used for this study, following the quantitative and qualitative approaches and applied a purposive sampling mechanism to identify the forest plot for this study and convenient sampling method for interviewing visitors. The computer software was used to process the coded data and accommodated traditional statistical tools to analyze the same. The results revealed that the existing potential for ecotourism development in the area was under-utilized and 90% of the identified challenges, such as deforestation, solid waste disposal (plastics and polythene) and clearing forest area for cardamom/ginger cultivation etc., have been observed at an extensive level, which are due to the human activities. According to the surveyed, 70% at Pitawalpatana, 65% at Maningala and 75% at Ilukkumbura disclosed that the said area was a very attractive and interesting place for nature lovers. The local visitor expresses that 70% of them are satisfied with nature-based attractions in the forest, 56% desire to visit to the Knuckles again, 42% has a moderate desire to visit again, 8% states that they do not like to visit again and 49% states that they have visited Knuckles more than one time. It is recommended to formulate an integrated forest management system to mitigate and manage challenges and to promote ecotourism in the Knuckles area in a sustainable manner with the collaboration of reverent stakeholders.
Keywords: Ecotourism; Sustainability; Biodiversity; Knuckles Mountain Range; Deforestation and Stakeholders